Conector urbano : infraestructura de transporte como nodo de conexión de espacios fragmentados (2017)
In a city with big problems in mobility like Bogota, the "METRO" it's going to be a solution that will change the massive transport in the city and the urban environment. For these reason one of the biggest challenges, is to connect all the transport methods and to activate the borders with other services that will serve the community. The project "Urban connector" located in the intersection of two great roads (Av Primera de Mayo and AV 68) seeks to solve some of the problems of the zone, like the division of the Neighborhoods by the great ways, the lack of connection of green spaces, the deficit of cultural facilities, and also connect al the transportation methods that converge in the zone, like transmilenio, the metro, the SITP, the commuter train, the bicycles, with the pedestrians, one library, a community Center and the divided parks.--Tomado del Formato de Documento de Grado.